Identification of lactic acid bacteria isolated from traditional cheeses of the Black Sea Region - Selin Kalkan; Gökhan Özdemir; Kadriye Özcan; Emel Unal Turhan (Revista Científica)
The aim of this study was to isolate and to identify lactic acid bacteria from traditional cheeses of the Black See Region. Artvin Şor, Giresun Tecen, Kargı Tulum, Ordu Kesik and Trabzon Telli cheese were used as cheese samples of the Black Sea Region. The number of lactic acid bacteria in traditional cheese of the Black Sea Region were ranged from 4.62 ± 0.76 and to 7.87 ± 0.64 log cfu·g-1. Gram–positive and catalase–negative colonies were evaluated as lactic acid bacteria based on the morphological and biochemical properties. According to biochemical analysis results, 39 lactic acid bacteria strains were identified by 16S rDNA isolated from cheese samples. Based on the sequence analysis, the indigenous lactic acid bacteria population was identified as Enterococcus faecium (35.9%), as Levilactobacillus brevis (12.8%), as Lactiplantibacillus plantarum (15.3%), as Pediococcus acidilactici (7.6%), as Enterococcus durans (7.6%), as Lacticaseibacillus paracasei (5.1%), as Lacticaseibacillus casei (7.6%), as Leuconostoc mesenteroides (2.5%), as Leuconostoc lactis (2.5%) and as Weissella cibaria (2.5%). Enterococcus spp. was the dominant lactic acid bacteria in cheese sample. The present findings revealed that lactic acid bacteria populations varied depending on cheese types in terms of cell counts and diversity.